A novel dynamic framework for subgrid scale parametrization of mesoscale eddies in quasigeostrophic turbulent flows. (1st August 2017) - Maulik, Romit; San, Omer
Abstract: This paper puts forth a modular dynamic subgrid scale modeling framework for large eddy simulation of quasigeostrophic turbulence based on minimizing the errors between structural and functional subgrid scale models. The approximate deconvolution (AD) procedure is used to estimate the free modeling parameters for the eddy viscosity coefficient parameterized in space and time using the Smagorinsky and Leith models. The novel idea here is to estimate the modeling parameters using the AD method rather than the traditionally used test filtering approach. First, a-priori and a-posteriori analyses are presented for solving a canonical homogeneous isotropic decaying turbulence problem. The proposed model is then applied to a wind-driven quasigeostrophic four-gyre ocean circulation problem, which is a standard prototype of more realistic ocean dynamics. Results show that the proposed model captures the quasi-stationary ocean dynamics and provides the time averaged four-gyre circulation patterns. Taking locally resolved flow characteristics into account, the model dynamically provides higher eddy viscosity values for lower resolutions.